CanCon and the Canon - Elliott, Robin (Canadian University Music Review / Revue de musique des universités canadiennes)

(untitled) (Canadian University Music Society / Société de musique des universités canadiennes, 2003)
Canadian music is almost completely absent from university-level textbooks used in this country, most of which are published in the United States. Canadian content typically is added to a music history survey course, if at all, at the end of the chronological account. This article argues for a different approach, one in which Canadian content is integrated into the survey course from the medieval era to the present day. Introductory courses in ethnomusicology could also include Canadian music materials at many different points.